Предмет: Математика,
автор: Аноним
Упрости выражение 5y(2y-1)-(3y-1)(3y+1)+(y-3)²
и вычисли его значение если y=-3
Ответы
Автор ответа:
0
5y(2y - 1) - (3y - 1)(3y + 1) + (y - 3)² = 10у² - 5у - (9у² - 1) + у² - 6у + 9 =
= 11у² - 11у + 9 - 9у² + 1 = 2у² - 11у + 10
при у = -3 получим: 2 · (-3)² - 11 · (-3) + 10 = 2 · 9 + 33 + 10 = 18 + 43 = 61
= 11у² - 11у + 9 - 9у² + 1 = 2у² - 11у + 10
при у = -3 получим: 2 · (-3)² - 11 · (-3) + 10 = 2 · 9 + 33 + 10 = 18 + 43 = 61
Похожие вопросы
Предмет: Информатика,
автор: gfhfdggr46
Предмет: Алгебра,
автор: loreasmaldonij
Предмет: Физика,
автор: TvoiOtvet
Предмет: Алгебра,
автор: Аноним